Duct infiltrative carcinoma of mamma in men. A Case report - Víctor Manuel Medina Pérez; María Caridad Navarro Otero; Miguel Ángel Rodríguez Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Mammary cancer in men is a rare and infrequent, fact-finding limited disease. The first well-informed case was described in England in XIV century by John Arderne. The factors that predispose the risk seem to include the exposition to radiation, the administration of estrogens and diseases related with the hyperestrogenism, like cirrhosis or Klinefelter's syndrome. A 61 year old patient is presented from an urban area with apparent background of health that noted ulceration in the nipple with secretion that was crushing the shirt. A diagnosis protocol of breast cancer was applied and a duct infiltrative carcinoma of mamma was diagnosed. Surgical treatment and chemotherapy were accomplished. In this moment he shows a favourable evolution with stable disease and adjuvant treatment with tamoxifeno.